The Relevance of African Concept of Theological Understanding of the Cross: Towards African Christian Theology (Global Journal of Human-Social Science, 2019)
This paper started with Paul's idea on the meaning of the cross. The author tries to look at the teaching of Paul on the meaning of the cross and briefly looking at the modern view of the event on the cross. He also X-ray the contribution of African culture in throwing high on the context of Africa on the matter of the cross and the understanding of African culture in atonement. In this paper the author also exposed the belief of African's on the matter regarding death as a positive and fulfillment of life. The shedding of the blood of Christ may be seen as throwing high and strengthening the community, through their ancestor. On the whole as Paul's understanding of the cross expressed in the context of his Jewish background, so the gospel must be expressed in terms of the culture of Africans.